Reduced plasma orexin-A levels in patients with bipolar disorder - Tsuchimine, Shoko (Neuropsychiatr Dis Treat, 2019)
PURPOSE: Orexins are hypothalamic neuropeptides involved in the regulation of sleep, appetite and arousal. An altered orexin system has been implicated in the pathophysiology of psychiatric disorders. This study aimed to examine whether plasma orexin-A levels differ in patients with schizophrenia, major depressive disorder (MDD), or bipolar disorder (BD) compared to in healthy controls. We also examined the possible correlations between plasma orexin-A levels and clinical variables. PATIENTS AND METHODS: All participants were Japanese. The sample consisted of 80 patients with schizophrenia (42 women, 52.5%; mean age 36.8 years), 80 patients with MDD (43 women, 53.8%; 43.7 years), and 40 patients with BD (24 women, 60%; 41.1 years), as well as 80 healthy controls (48 women, 60%; 47.0 years). Plasma orexin-A levels were quantified by an enzyme-linked immunosorbent assay. RESULTS: Mean orexin-A levels were significantly different across the four diagnostic groups (F=4.09; df=3; p=0.007, η(2)=0.06). In particular, the patients with BD showed significantly lower orexin-A levels than did the controls. When the median value of the control group (109.8 pg/ml) was set as a cut-off value, subjects whose orexin-A levels were below the cut-off were more common in all psychiatric groups (schizophrenia: 73.8%, x(2)=9.56, df=1, p=0.003, OR=2.81, 95% CI: 1.45 to 5.45, d=0.57; MDD: 78.5%, x(2)=14.02, df=1, p<0.001, OR=3.65, 95% CI: 1.82 to 7.29, d=0.72; BD: 87.5%, x(2)=16.0, df=1, p<0.001, OR=7.00, 95% CI: 2.49 to 19.70, d=1.07). We found no association between plasma orexin-A levels and any clinical symptoms, depression severity, or medication doses. CONCLUSION: Our results suggest that plasma orexin-A levels are reduced in patients with BD.